Synthesis, Characterization and Evaluation of the Transformations in Hibiscus sabdariffa-graft-poly(butyl acrylate) - B. S. Kaith; Aashish Chauhan (E-Journal of Chemistry)
Different reaction parameters for the graft copolymerization of butyl acrylate onto Hibiscus sabdariffa fiber were optimized. Graft copolymers thus obtained were subjected to characterization using XRD, TGA, DTA, SEM and FTIR techniques and were evaluated for physio-chemical changes in the behavior. The percentage crystallinity and crystallinity index were found to decrease with increase in grafting while there was reduction in moisture absorption and increase in chemical, thermal resistance of the graft copolymers.